Nyadran Tradition in Cepokokuning Village: Educational Construction of Local Wisdom in Islamic Values - M. Yasin Abidin,; Rofiqotul Aini,; Andung Dwi Haryanto, (Jurnal Pendidikan Agama Islam Al-Thariqah, 2022)
This study intends to explain the series of nyadran traditions in Cepokokuning village, and to find out the community’s understanding of the integration of Islamic values ​​and local wisdom into the nyadran tradition. The design of this research method is qualitative with a phenomenological approach. The findings of this study conclude that before the covid-19 pandemic, the construction of local wisdom on Islamic values ​​in the nyadran tradition in Cepokokuning Village before the covid-19 pandemic was shown in goat slaughtering activities on the banks of the river near the dam, praying together, and pilgrimages in the area. the graves of the ancestors, salvation at crossroads (baritan), and watching puppet entertainment together in front of the Cepokokuning village hall. Meanwhile, during the Covid-19 pandemic, the nyadran tradition was carried out as usual, but the slaughter of goats was only attended by representatives of the residents, ziyarah (nyekar) was carried out independently, salvation (baritan) was held at the mosque, while puppet entertainment activities were abolished. The understanding of the people of Cepokokuning Village towards the values ​​of local wisdom and Islamic values ​​in the nyadran tradition is shown in the earth alms tradition which they believe is a wasilah for health and safety. According to them, the nyadran tradition has been practiced for generations and does not conflict with local wisdom and sharia values. The Islamic values ​​found in the nyadran tradition are togetherness, harmony, egalitarian, mutual cooperation, deliberation, alms, draw closer to Allah as gratitude to Him